Where and what arteries are most likely injured with pelvic fractures?: The Influence of Localization, Shape, and Fracture Dislocation on the Arterial Injury During Pelvic Fractures. Issue 5 (2nd April 2019) - Kachlik, David; Vobornik, Tomas; Dzupa, Valer; Marvanova, Zuzana; Toupal, Ondrej; Navara, Eduard; Stevulova, Nikoleta; Baca, Vaclav
Abstract : Blood vessels passing through pelvic region come into intimate contact with pelvic bone and can be injured by the sharp edges of the dislocated fracture fragments. The aim of the study was to evaluate the influence of localization, shape, and dislocation of individual pelvic ring bones' fractures on arterial injuries. The study group consisted of 474 patients enrolled in a 1‐year prospective multicenter study. The pattern of pelvic fracture lines was characterized and recorded on a planar diagram of the subjected side of the pelvis. The diagram was subdivided into 11 designated areas. Frequency of injury at each 11 areas was recorded. The course of individual arteries in the 11 areas was also recorded in relation to each type of pelvic fractures. Out of the 474 investigated patients, the highest proportion of fractures occurred in the areas of the superior (62%) and inferior (59%) ramus of the pubis as well as in the lateral part of the sacrum (19%). These locations can be associated with injuries of the external iliac, obturator, internal iliac, and aberrant obturator arteries. The highest risk of arterial injuries was associated with vertically displaced fractures in the middle part of the superior and inferior pubic rami, along the ischial ramus, in the apex of the greater sciatic notch and in the vicinity of the ventral part of the sacroiliac joint, where the artery runs at a distance of less than 1 cm from the bone. Clin. Anat. 32:682–688, 2019. © 2019 Wiley Periodicals, Inc.